Association of neutrophil-to-lymphocyte ratio and neutrophil activation with treatment response in neovascular AMD - Alexander Kai Thomsen; Maria Abildgaard Steffensen; Kathrine Gotfredsen; Henrik Vorum; Bent Honoré; Mogens Holst Nissen; Torben Lykke Sørensen (AJO International)
Purpose: The neutrophil-to-lymphocyte ratio (NLR) and alterations of activation surface markers on circulating neutrophils have been suggested to be involved in the pathogenesis of age-related macular degeneration (AMD). The aim of this study was to investigate the relationship between NLR, activation surface markers on neutrophils, AMD stage, and treatment response in neovascular AMD (nAMD). Design: Prospective cohort study. Methods: Treatment-naïve nAMD patients, intermediate AMD (iAMD) patients, and healthy controls were consecutively enrolled. Treatment response in nAMD patients was categorized as good, partial and poor based on change of retinal fluid and central retinal thickness. Treatment response was evaluated after the loading phase and after one year of treatment with aflibercept 2 mg. NLR and activation surface markers on circulating neutrophils (CD11a, CD11b, CD31, CD66b, CD162, and CD182) were examined with flow cytometry. NLR and activation surface markers were compared between healthy controls, iAMD, and nAMD patients, as well as between nAMD treatment response groups. Polymorphisms in the CFH and ARMS2 genes were compared to NLR and the surface markers in nAMD patients. Results: NLR was significantly elevated in nAMD patients compared to healthy controls (P < 0.001). nAMD patients with poor 1-year treatment response had a significantly higher NLR compared to good 1-year treatment responders. Expression levels of CD11a, CD11b, CD31, CD66b, CD162, and CD182 on circulating neutrophils were elevated in nAMD patients compared to healthy controls (all P < 0.05), however no significant differences were found between nAMD treatment response groups. No significant associations were found between CFH or ARMS2 genotypes with NLR or neutrophil surface markers in nAMD patients. Conclusion: Elevated NLR was associated with a poor 1-year treatment response. The NLR and expression levels of activation surface markers on circulating neutrophils were significantly elevated in treatment-naïve nAMD patients compared to healthy controls.